2016
DOI: 10.1111/fwb.12855
|View full text |Cite
|
Sign up to set email alerts
|

Colony persistence in waterbirds is constrained by pond quality and land use

Abstract: Summary The conservation of wetlands, many threatened by human activities, is paramount to sustaining global biodiversity. Yet the protection of targeted wetlands may not be sufficient to protect the species they host because some species may also be impacted by alterations to the surrounding landscape. Some black‐headed gull (Chroicocephalus ridibundus: Laridae) populations have experienced a sharp decline in population size and number of colonies. Here, we investigated the relative contributions of wetland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…Specialization coefficients correspond to the breadth of the habitat preferences of the species (Francesiaz et al, 2017). MNDW was the most important among EGV for specialization 1 axis at landscape level.…”
Section: Discussionmentioning
confidence: 99%
“…Specialization coefficients correspond to the breadth of the habitat preferences of the species (Francesiaz et al, 2017). MNDW was the most important among EGV for specialization 1 axis at landscape level.…”
Section: Discussionmentioning
confidence: 99%
“…A study in the Florida panhandle found that natural streams, altered streams, and ditches within the same forested region had similar macroinvertebrate and fish assemblages [100]. Agricultural intensification around fishponds has contributed to the rapid decline in breeding populations of black-headed gulls (Chroicocephalus ridibundus) in central France [101]. More such comparisons between artificial and natural waterbodies in similar settings are needed to disentangle the effects of watershed setting from other factors that influence the condition of artificial aquatic systems.…”
Section: Settingmentioning
confidence: 99%
“…For example, Morimoto et al (2006) found that two woodland bird species prefer woodlands surrounded by agricultural areas over those surrounded by urban areas. Francesiaz et al (2017) found that gulls prefer ponds surrounded by meadow and fallow land rather than woodland. Dallimer et al (2010) found that the size of urban area and the amount of grassland patches affect the richness of moorland bird species in northern England.…”
Section: Introductionmentioning
confidence: 99%